DISSEMINATION OF FAKE NEWS REGARDING HALAL AND “DAMAGE CONTROL” AMONG POLICYMAKERS AND HALAL INDUSTRY PLAYERS IN MALAYSIA - Noraini Junoh,; Zanirah Mustafa@Busu,; Norazmila Yusuf,; Alifah Hanin Pozlan, (Journal of Islamic, Social, Economics and Development, 2023)
The advancement technology surprising fast in modern era were taking place in daily task of human life. All of information would easily and quick to gain from online sources as easy lifting a finger. However, despite the rapid development of science and technology and its potential in Halal industry, there are one issues that relevant to discuss which is dissemination of fake news regarding Halal matter. This was truly mainstream happened that nevertheless affected Halal industry in aspect of religious trustworthiness and economic sustainability. Hence, this study intends to identify the method used by policymakers in managing fake news and the impactful that burden the damage by Halal industry players and also to facilitate solutions in prevention issues that occur in Halal industry. This research was qualitative which in conceptual study of format. The research managed to figure out that Policymakers have several procedures in handling fake news and the implication towards Halal industry player was ultimately harm the brand reputation. Therefore, tabayyun concept should be applied and develop Halal awareness among community.